INVESTIGATING MANAGEMENT OF WASTE IN GOVERNMENTAL MEDICAL AND HYGIENIC CENTERS OF FARASH BAND'S CITY - SHAHRYARE, SHADPOOR; Zare, karim; GHAVAM, ABBAS (International Journal of Clinical and Biomedical Research, 2016)
Introduction: Growth of urbanization has led to changes in production and components of nosocomial wastes and proper management of repelling solid wastes is an issue that has direct relationship to health and infection's control in society. Although the numbers of these materials are low, but can cause lots of dangers. This study has been done with the aim of determining quantity and quality and also condition of management of wastes at medical and hygienic centers in year 94. Methodology: In this descriptive-sectional study that performed at governmental hygienic and medical centers of Farash Band, productive wastes divided into 3 main groups and the condition of wastes management was also investigated on the basis of prepared check list from management's regulation of nosocomial wastes. By using panel regression, the effect of various variables on rate of infectious wastes and all the productive and nosocomial wastes was analyzed. Results: Findings of study showed that productive wastes are related to the numbers of referred people and are more than other hygienic and medical centers in hospitals. Although a meaningful relation between the rate of productive and infectious wastes and the numbers of referred people has not been observed, but the rate of productive and infectious waste in hospitals was more than other centers and it was statistically meaningful. Conclusion: Daily productions of thousands tons of waste in different areas (of country) and all kinds that they have according to pollution, are an issues that considering population's growth and development of industry and technology should be placed at up to hygiene and environment's plans of the country. According to the importance of this issue, at first items about hygienic dangers, type and the rate of waste and then collection and excretion systems should be noticed.